Wear debris: basic features and machine health diagnostics - Khan, M. A.; Starr, Andrew G. (British Institute of Non-destructive Testing, 2006)
Modern high speed and power machinery components like gears, bearings, pumps, hydraulics and motors normally suffer from wear phenomena during operation. The study of wear debris can help estimate the condition of the surface of a component, so its basic features may be used to diagnose component health prior to failure. In this paper, a review is presented of the current literature related to wear debris and its analysis. The basic features of wear debris are highlighted, and their possible potential to diagnose the health of machine components is discussed. The basic features of wear debris have been classified with respect to the approach of measurement for component health diagnostics. In addition, each feature has been detailed with its possible measurement descriptors, its trend during machine component operation, and its distinct health diagnostics capability. Finally the paper proposes advances in machine component health diagnostics solution, by optimising the diagnostic capabilities of basic wear debris features.
Keywords: Wear; wear debris basic features; wear debris detection descriptors; machine component health